Gradualism and Liquidity Traps - Sebastian Schmidt; Taisuke Nakata (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Modifying the mandate of a discretionary central bank to include an interest-rate smoothing objective increases the welfare of an economy where large contractionary shocks occasionally force the central bank to lower the policy rate to its effective lower bound. The central bank with an interest-rate smoothing objective credibly keeps the policy rate low for longer than the discretionary central bank with the standard mandate does, as in optimal commitment policy. Through expectations, the temporary overheating of the economy associated with such low-for-long interest rate policy mitigates the declines in inflation and output when the lower bound constraint is binding. In a calibrated model, we find that the introduction of an interest-rate smoothing objective can reduce the welfare costs associated with the lower bound constraint by more than half.
Keywords: E52; E61; E58; 330